Antibiotic resistance pattern among aerobic bacterial isolates from osteomyelitis cases attending a Tertiary care hospital of North India with special reference to ESBL, AmpC, MBL and MRSA production - Khatoon, Razia; Khan, Shameem Ahmad; Jahan, Noor (International Journal of Research in Medical Sciences, 2017)
Background: Osteomyelitis is a common cause of morbidity in developing countries. Its treatment comprises of surgical debridement of all necrotic bone and soft tissue along with use of appropriate antimicrobial therapy. Treatment is becoming increasingly troublesome due to rise in drug resistant isolates in osteomyelitis cases. The present study was done to determine the antibiotic resistance pattern among aerobic bacterial isolates from osteomyelitis cases. Methods: 125 samples from osteomyelitis cases were aerobically cultured and isolates from culture positives were identified by standard procedures. Antimicrobial susceptibility testing was done by Kirby Bauer disk diffusion method. Staphylococcal isolates were screened for methicillin resistance and Gram negative bacilli were screened and confirmed for ESBL, AmpC and MBL production. Results: Out of 125 samples cultured, 20 were culture negative and 105 were culture positive giving rise to 120 isolates (58 Gram positive and 62 Gram negative organisms). The prevalence of methicillin resistant staphylococcal (MRS) isolates, ESBL, AmpC and MBL producers was found to be 43.1%, 51.6%, 24.2% and 14.5% respectively. All the resistant isolates were multidrug resistant, with MRS being 100% sensitive only to vancomycin, linezolid and teicoplanin, ESBL and AmpC producers being 100% sensitive only to imipenem and colistin, and MBL producers being 100% sensitive only to colistin. Conclusions: Antibiotic therapy on the basis of antibiotic susceptibility pattern helps the clinician to choose appropriate drugs leading to successful treatment and prevention of emergence and dissemination of drug resistant isolates.